New Management in Bilateral Masseter Muscle Hypertrophy. Issue 4 (December 2017) - Bocchialini, Gabriele; Castellani, Andrea; Negrini, Stefano; Rossi, Alessandro
Bilateral masseter muscle hypertrophy is an alteration in shape and thickness of the masseter muscles that can modify the width of the lower face causing aesthetic and functional problems. A 21-year-old man was referred to the Department of Maxillofacial Surgery at the Civil Hospital in Brescia by his dentist for an evaluation of his facial appearance with a square-face type. To reduce the undesirable facial appearance, a surgical intraoral approach was performed; the procedure includes the bilateral dissection of the masseter muscle, partial lipectomy, and the ostectomy of the mandibular angle assisted by a surgical guide built on a stereolithographic model. The patient was satisfied with the functional and aesthetic outcomes of both the profile and the frontal views. There was no evidence of complication at a 1-year follow-up. This new method yields optimal aesthetic results with an enhanced outline of the lower face.